The Association between Grand Multiparity and Adverse Neonatal Outcomes: A Retrospective Cohort Study from Ha'il, Saudi Arabia - Hend Alkwai; Farida Khan; Reem Alshammari; Asma Batool; Ehab Sogeir; Fahaad Alenazi; Khalid Alshammari; Ayesha Khalid (MDPI AG, 2023)
Inconsistent evidence exists regarding the association of grand multiparity with adverse neonatal outcomes. This study aims to compare specific adverse outcomes in grand multiparas (those with five or more births at twenty or more weeks of gestation, regardless of fetal outcome) compared to those with lower parity (those with less than five births at twenty or more weeks of gestation, regardless of fetal outcome). A retrospective cohort study was undertaken at the Maternity and Children Hospital in Ha'il region, Saudi Arabia. After calculating the required sample size, data were collected from consenting participants with a viable singleton delivery. Socio-demographic variables, select maternal characteristics, and adverse neonatal outcomes (admission to the neonatal intensive care unit, low birth weight, prematurity, and APGAR score less than 7 in the first 5 min) were compared between grand multiparas and women with lower parity. Two hundred ninety-four participants were recruited (ninety-eight grand multiparas and one hundred ninety-six of lower parity). There was a statistically significant difference between the two groups in relation to age, level of education, body mass index, and the occurrence of gestational diabetes. Out of the studied adverse neonatal outcomes after the adjustment for maternal age between the two groups, no statistically significant difference in the adverse neonatal outcomes was found between the two groups. Grand multiparity does not incur an additional risk of adverse neonatal outcomes compared to women of lower parity. Furthermore, increasing maternal age and comorbid conditions might have a more detrimental effect on neonatal outcomes than grand multiparity per se.